A systematic review of graduate student peer mentorship in academia. Issue 5 (20th October 2019) - Lorenzetti, Diane L.; Shipton, Leah; Nowell, Lorelli; Jacobsen, Michele; Lorenzetti, Liza; Clancy, Tracey; Paolucci, Elizabeth Oddone
ABSTRACT: While researchers have suggested that mentorship positively affects academic and learning outcomes in higher education, little is known about the impact of peer mentoring on graduate students' academic experiences. We conducted a systematic review to explore the impact of peer mentorship on graduate students' learning, and formal approaches to enhancing these relationships. We searched eight multidisciplinary databases to identify relevant studies. Studies were included if they reported on graduate students' peer mentoring, or evaluated initiatives to further the development of these relationships. Forty-seven studies were included in this review. The majority of students who participate in formal peer-mentoring programs benefit from these experiences. Peer mentorship positively affects developmental outcomes across four domains of graduate learning: academic, social, psychological, and career. While group-mentoring may be an effective means of delivering peer-mentorship support, further evaluative research is required to determine how academic institutions can promote positive peer mentoring relationships in graduate education.